Preparation of rare earth iodates and their decomposition activity on organic dyes and antibacterial/antiviral activities. (1st May 2023) - Abe, Kazuya; Sunada, Kayano; Mochizuki, Yasuhide; Isobe, Toshihiro; Matsushita, Sachiko; Nagai, Takeshi; Ishiguro, Hitoshi; Nakajima, Akira
Abstract: After amorphous Ce(IO3 )4 powder was prepared using precipitation method at room temperature, powder samples of crystalline Ce(IO3 )3, α-La(IO3 )3 and δ-La(IO3 )3 were prepared by calcining the precipitates formed by mixing the solutions. All samples eluted some constituent ions in the solution. The Ce(IO3 )4 decomposed methylene blue and methyl orange in water in the dark. The valence of Ce measured before and after the decomposition reaction suggested oxidative decomposition by Ce(IV). These samples exhibited high antibacterial activity against Escherichia coli and Staphylococcus aureus, and also high antiviral activity against the non-enveloped virus bacteriophage Qβ and the enveloped virus bacteriophage Φ6. Moreover, these samples caused protein denaturation. It is conceivable that the adsorption of lanthanum and cerium ions leaked from the sample, the oxidation power of ions such as Ce(IV) and IO3 −, and pH value affected these antibacterial and antiviral activities.